Synthesis, In Silico and In Vitro Characterization of Novel N,N-Substituted Pyrazolopyrimidine Acetamide Derivatives for the 18KDa Translocator Protein (TSPO) - Jaekyung Park; Sobia Wasim; Jae Ho Jung; Mi-hyun Kim; Byung Chul Lee; Mohammad Maqusood Alam; Sang-Yoon Lee (MDPI AG, 2023)
The translocator protein (TSPO) is an interesting biological target for molecular imaging and therapy because the overexpression of TSPO is associated with microglial activation caused by neuronal damage or neuroinflammation, and these activated microglia are involved in various central nervous system (CNS) diseases. The TSPO is a target for neuroprotective treatment, which is used with the aim of reducing microglial cell activation. The novel N,N-disubstituted pyrazolopyrimidine acetamides scaffold (GMA 7-17), which bears a fluorine atom and is directly linked to the phenyl moiety, was synthesized, and each of the novel ligands was characterized in vitro. All of the newly synthesized ligands displayed picomolar to nanomolar affinity for the TSPO. Particularly, an in vitro affinity study led to the discovery of 2-(5,7-diethyl-2-(4-fluorophenyl)pyrazolo [1,5-a]pyrimidin-3-yl)-N-ethyl-N-phenylacetamide GMA 15 (Ki = 60 pM), a novel TSPO ligand that exhibits a 61-fold enhancement in affinity compared to the reference standard DPA-714 (Ki = 3.66 nM). Molecular dynamic (MD) studies of the highest affinity binder, GMA 15, were carried out to check its time-dependent stability with the receptor compared to DPA-714 and PK11195. The hydrogen bond plot also indicated that GMA 15 formed higher hydrogen bonds compared to DPA-714 and PK11195. We anticipate that further optimization to enhance the potency in a cellular assay needs to be followed, but our strategy of identifying potential TSPO binding novel scaffolds may open up a new avenue to develop novel TSPO ligands suited for potential molecular imaging and a wide range of therapeutic applications.